2001
DOI: 10.1126/science.293.5527.98
|View full text |Cite|
|
Sign up to set email alerts
|

A β 2 Adrenergic Receptor Signaling Complex Assembled with the Ca 2+ Channel Ca v 1.2

Abstract: The existence of a large number of receptors coupled to heterotrimeric guanine nucleotide binding proteins (G proteins) raises the question of how a particular receptor selectively regulates specific targets. We provide insight into this question by identifying a prototypical macromolecular signaling complex. The beta(2) adrenergic receptor was found to be directly associated with one of its ultimate effectors, the class C L-type calcium channel Ca(v)1.2. This complex also contained a G protein, an adenylyl cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
535
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(558 citation statements)
references
References 27 publications
23
535
0
Order By: Relevance
“…For example, it has been demonstrated that in hippocampus neurons, β 2 adrenergic receptor, calcium channels, G protein, adenyl cyclase and other proteins are co-localised [70]; however, these clusters of proteins are not recognised as partitioning into rafts. The authors conclude that "co-localisation of GPCRs with their ultimate targets in macromolecular complexes could be a general mechanism to ensure that signalling is both specific and fast" [70]. Note that due to the indirect methodologies used to reach this conclusion one cannot infer the microscopic mechanism responsible for co-localisation.…”
Section: Examples Of Observed Protein Confinementsmentioning
confidence: 99%
“…For example, it has been demonstrated that in hippocampus neurons, β 2 adrenergic receptor, calcium channels, G protein, adenyl cyclase and other proteins are co-localised [70]; however, these clusters of proteins are not recognised as partitioning into rafts. The authors conclude that "co-localisation of GPCRs with their ultimate targets in macromolecular complexes could be a general mechanism to ensure that signalling is both specific and fast" [70]. Note that due to the indirect methodologies used to reach this conclusion one cannot infer the microscopic mechanism responsible for co-localisation.…”
Section: Examples Of Observed Protein Confinementsmentioning
confidence: 99%
“…To rule out the possibility of GST having a role in multimerization, PDZ1 was cleaved from GST by using (10) and is likely to be in the complex. On agonist activation of the receptor, adenylate cyclase is stimulated through the Gs pathway (33), leading to an increase in highly compartmentalized cAMP. This increased local concentration of cAMP leads to the activation of PKA, which is in close proximity to CFTR (36), leading to a compartmentalized and specific signaling of the channel.…”
Section: Fig 3 Macromolecular Complex Of Cftr and ␤2ar Is Mediated mentioning
confidence: 99%
“…Synaptic stimulation under these conditions should not enhance depolarization so it is unclear why synaptic stimulation is necessary. Recent results show that L-type VDCC in hippocampal neurons can be strongly upregulated by norepinephrine (Davare et al, 2001). One possibility is that synaptic stimulation led to the release of norepinephrine, and thereby enhanced Ca 2ϩ entry through VDCC.…”
Section: What Is the Role Of Vdcc In Ltp?mentioning
confidence: 99%